An Improved Method for Extracting Viruses From Sediment: Detection of Far More Viruses in the Subseafloor Than Previously Reported - Pan, Donald; Morono, Yuki; Inagaki, Fumio; Takai, Ken (Frontiers in Microbiology, 2019)
Viruses are the most abundant biological entities on Earth and perform essential ecological functions in aquatic environments by mediating biogeochemical cycling and lateral gene transfer. Cellular life as well as viruses have been found in deep subseafloor sediment. However, the study of deep sediment viruses has been hampered by the complexities involved in efficiently extracting viruses from a sediment matrix. Here, we developed a new method for the extraction of viruses from sediment based on density separation using a Nycodenz density step gradient. The density separation method resulted in up to 2 orders of magnitude greater recovery of viruses from diverse subseafloor sediments compared to conventional methods. The density separation method also showed more consistent performance between samples of different sediment lithology, whereas conventional virus extraction methods were highly inconsistent. Using this new method, we show that previously published virus counts have underestimated viral abundances by up to 2 orders of magnitude. These improvements suggest that the carbon contained within viral biomass in the subseafloor environment may potentially be revised upwards to 0.8-3.7 Gt from current estimates of 0.2 Gt. The vastly improved recovery of viruses indicate that viruses represent a far larger pool of organic carbon in subseafloor environments than previously estimated.